The effect of incorporating high reflectance pigments in thermal enhanced exterior finishing systems - Nuno M. M. Ramos (2019)
In the recent years, the concerns on building thermal performance tend to follow the challenges imposed by more demanding building design. The increase of new building materials and technologies with improved thermal characteristics, such as ETICS, thermal mortars and high reflectance coatings, contribute to meet the thermal requirements, by lowering the façade U-value and/or the surface temperature variation. This paper has the objective of evaluating the effect of incorporating high reflectance pigments in organic coatings applied in thermal systems, such as ETICS and thermal rendering. The effect on the thermal behaviour is also discussed by comparing them with a non-insulated system. The solar absorptance and the surface temperature of different façade systems with distinct coatings were measured "in situ". The solar absorptance was measured with a pyranometer with an adapted methodology based on the ASTM E1918 standard. The surface temperature of the specimens was continuously monitored for an extended period enabling a comparison under different climatic conditions. The results showed that the incorporation of high reflectance pigments allowed a significant decrease of the solar absorptance even in darker colours and that the absence of thermal insulation proved to have a significant effect on the surface temperature.